Entrepreneurial Profile and Constraint Analysis of Farm and Non-farm Sectors Entrepreneurial Training Programmes in Krishi Vigyan Kendra and Rural Development & Self Employment Training Institute - Kobba, F; Nain, M S; Singh, Rashmi; Mishra, J R; Shitu, G A (Indian Journal of Extension Education, 2020)
Research has proven that entrepreneurship can boost the economy of many nations, this has not been true for many due to the challenges that impede entrepreneurship in both the farm and non-farm sectors. An interview schedule was used to collect information from 120 entrepreneurs, (60 farm and 60 non-farm entrepreneurs). In RUDSETI farm sector, 66.6% of the entrepreneurs had an annual income of less than 1 lakh whereas, in the non-farm sector, half (50.0%) of the entrepreneurs had an annual income of more than 3 lakh. In KVK, farm sector, 46.7% of the entrepreneurs had an annual income of over 3 lakhs, whereas in the non-farm sector, 46.7% of the entrepreneurs had an annual income of 1-2 lakh. In RUDSETI farm and non-farm sectors, 100% and 50.0% of the entrepreneurs had 1-3 years of entrepreneurial experience, respectively. Similarly, in the KVK farm and non-farm sectors, 53.3% and 76.7 % of the entrepreneurs had an entrepreneurial experience of 1-3 years, respectively. The highest-ranked constraint in the farm sector was lack of market information (71.0%) and lack of financial resources (69.5%) whereas, the non-farm sector, lack of market information (68.1%) and lack of financial resources (63.4%) had the highest rank.